Production of stable isotope labelled lipase Lip2 from Yarrowia lipolytica for NMR: Investigation of several expression systems - Nars, G.; Saurel, O.; Bordes, F.; Saves, I.; Remaud-Siméon, M.; André, I.; Milon, A.; Marty, A. (Protein expression and purification, 2014)
•Yarrowia lipolytica, Pichia pastoris, Escherichia coli and cell free expression were tested.•Yarrowia lipolytica was the most efficient system for production of 15N labelled Lip2.•First 15N–1H HSQC spectra of Lip2 was recorded. Extracellular lipase Lip2 from Yarrowia lipolytica is a promising biocatalyst with unusual structural features, as indicated by X-ray crystallography. These features comprise a mobile domain called the lid that controls access to the catalytic site. Conformational rearrangements of the lid have been suggested to regulate lipase enzymatic activities. We used nuclear magnetic resonance to investigate the dynamics of Lip2 by exploring four expression systems, Escherichia coli, cell-free, Pichia pastoris and Y. lipolytica to produce uniformly labelled enzyme. The expression of Lip2 was assessed by determining its specific activity and measuring 15N–1H HSQC spectra. Y. lipolytica turned out to be the most efficient expression system. Here, we report the first use of Y. lipolytica as an expression host for the production of uniform stable isotopic labelled protein for further structural and dynamics studies using NMR.